Anti-inflammatory effect of tamarind seed coat extract against LPS-induced RAW264.7 macrophages - Jirapa Puntarut; Wipawadee Sianglum; Supita Tanasawet; Pennapa Chonpathompikunlert; Wanida Sukketsiri (Penerbit Universiti Kebangsaan Malaysia, 2020)
Inflammatory response is modulated by stimulated immune cells, and has a pivotal role in host defense system against various stimuli. In this study, we evaluated the anti-inflammatory property of tamarind seed coat extract (TSCE) in lipopolysaccharide (LPS)-induced RAW264.7 macrophages. Various concentrations of TSCE (10, 25, and 50 µg mL-1) were applied and then stimulated with LPS (1 μg mL-1) in RAW264.7 macrophages and the level of reactive oxygen species (ROS) and nitric oxide (NO) were measured. Besides, enzyme-linked immunosorbent assay (ELISA) was used to measure the level of pro-inflammatory cytokines. Our results showed that TSCE suppressed LPS-induced intracellular ROS production and suppressed the NO levels in a dose-dependent manner. Significantly, the anti-inflammatory activity was correlated with a lowered LPS-stimulated TNF-α and IL-1β pro-inflammatory cytokines. These results implied that TSCE possess potent anti-inflammatory activity, which supported new insights into the TSCE utilization to protect inflammation-related disorders.